Efecto de tres niveles de cuyinaza en el rendimiento de zanahoria (Daucus carota L.)VAR. CHANTENAY ROYAL. En Santiago de Chuco, La Libertad - Velasquez Caro, David Elias (2017)
The present investigation was carried out during the months of October of 2015 to February of 2016 in the hamlet of Muycan, Sector San Juan de Yahuish, Province of Santiago de Chuco, La Libertad Region; Located at 3091 msnm, with rainfall during the months of December to April, whose temperature reaches 22 ° C on sunny days and at night descends to 05 ° C; The soil texture is frank sandy clay, with a pH that reaches 6.3, with a good percentage of organic matter (4.2%). The objective of the study was to evaluate the effect of three levels of cuyinase on the yield of carrot (Daucus carota L.) var. Chantenay Royal in Santiago de Chuco, freedom; Also, determine the level of cuyinaza that allows to obtain the greater yield. The treatments were as full: T0 without incorporating cuyinaza (control), T1 (03 t / ha) of cuyinaza, T2 06 (t / ha) of cuyinaza, and T3 09 (t / Ha) cuyinaza. The statistical evaluation was based on the analysis of variance and the tukey test, at 0.05% significance. The results indicate that the morphological and performance variables presented significant statistical difference; In which treatment (T2) was the best of all treatments, achieving a yield of 35000 kg.ha-1 and the best quality of Daucus Carota. Var. Chantenay Royal in the hamlet of Muycan- Santiago De Chuco-La Libertad.